Moral Hazard vs. Land Scarcity : Flood Management Policies for the Real World - Avner, Paolo; Hallegatte, Stephane (World Bank, Washington, DC, 2019)
This paper investigates the costs and benefits of three ex ante flood management strategies -- risk-based insurance, zoning, and subsidized insurance -- in an urban economics framework that takes land scarcity into account. In a theoretical setting and in the absence of market failures, risk-based insurance perfectly internalizes flood risks and maximizes social welfare. However, risk-based insurance faces major technical, social, and political challenges and is not always realistic. Flood zoning and subsidized insurance are two second-best options that are easier to implement and less technically demanding. The paper explores analytically and with numerical simulations the welfare losses and distributional impacts with these second-best options, and demonstrates that total losses often remain small. Flood zoning is close to optimal when flood-prone areas are small, floods are frequent, and housing quality is low. Zoning keeps total land value unchanged but transfers wealth from landowners in flood-prone areas to landowners in safe locations. Subsidized insurance is close to optimal when a large fraction of a city is flood prone, floods are rare, and housing quality is high. And although it increases flood losses through the moral hazard effect, subsidized insurance encourages more construction, which reduces housing rents and benefits tenants regardless of where they live. Subsidized insurance transfers wealth from landowners in safe locations to landowners in flood-prone areas. When the implementation of risk-based insurance is unrealistic, as is often the case in developing countries, a combination of zoning in high-risk areas and subsidized insurance for low-risk areas might be a good alternative.